ANALISA INTERKONEKSI SISTEM MENGGUNAKAN DlgSILENT (STUDI KASUS PLTU PULANG PISAU KALIMANTAN TENGAH) - Christine Widyastuti; Heri Suyanto; Dyan Retno Febrianini (Sekolah Tinggi Teknik - PLN, 2015)
One of the planned areas to be implemented is the construction of a 2x60 MW coal-fired steam power plant in Pulang Pisau District, Central Kalimantan. The development of this steam power plant aims to meet the demand for electricity in Central Kalimantan which has been supplied using barito systems and isolated isolated systems generated from diesel generators. The 80% own barito system is concentrated in South Kalimantan with an electrical interconnection system using 150 KV and 70 KV transmission lines covering South and Central Kalimantan that are connected to hydro, coal and diesel power plants. The other 20% is produced from Central Kalimantan, specifically the capital of Palangkaraya and Katingan regency. Based on the simulation done using DlgSILENT software on barito system after the entry of PLTU Pulang Pisau shows the total change of power supply and the occurrence of voltage changes where the peak load time before PLTU Pulang Pisau enter the total power system generated by 395.18 MW and then after PLTU Pulang Pisau Entered into the total power generation system to 411.14 MW. This value is close to the limit of the operating voltage value but the barito system's transmission rate capability is still sufficient to overcome the change in voltage rise.